(untitled) (Fiep Bulletin - online, 2011)
This is a work of literature review conducted on the website of the Virtual Health Library and Bank of theses and dissertations at the University of Sao Paulo. The objectives were to identify the scientific literature has been searched by the Scale of a Glasgow Coma Score (GCS) to measure the severity of traumatic brain injury (TBI), identified in the analyzed which professionals who research on the use of GCS and in which situations, identify articles published in the databases searched, the GCS is used alone is capable of measuring the severity of TBI. 65 studies were identified and selected 10. Most of the selected publications were indexed in LILACS and medical professionals were responsible for the publications related to the subject under study. We found that CT and physiological indices such as the RTS were the most common tools associated with the GCS and that had statistically significant results. We note that some studies using only the GCS failed to prove its real efficacy alone, but others have found significant predictions and actual use when the GCS in patients with severe TBI.